Citizenship and democratic culture in habitants from Arequipa, Peru - Banda Lazarte, Gonzalo (2022)
This research intends to value citizen and democratic culture in Arequipa based on certain sociodemographic variables. The Scale of Citizen and Democratic Culture (Arias & Banda, in press) was applied to 805 inhabitants of metropolitan Arequipa, and the data were analyzed comparatively according to sex, age, marital status, degree of education, and socioeconomic level. The results indicate that taking into account the marital status, the divorced, separated, and widowed have the highest scores in terms of the quality of government (F(3, 805) = 6.875, p <.001; η2 = .025), civic culture (F(3, 805) = 2.82, p = .038; η2 = .011) and freedom and democracy (F(3, 805) = 5.289; p = .001; η2 = .020). In addition, according to the socioeconomic level, people from the A/B segment presented lower scores in civic culture (F(3, 805) = 5.140, p = .002, η2 = .019); but they have the highest scores in freedom and democracy (F (3, 805) = 7.287, p <.001; η2 = .027). Likewise, according to the level of education, those evaluated with a higher level of education have the highest scores in freedom and democracy (F(2, 805) = 3.484, p = .031, η2 = .009). We conclude that sociodemographic variables such as marital status, socioeconomic level, and education are associated with the appreciation of the citizen and democratic culture of the people from Arequipa.